Improvements in the Design of the Cyclohexane Production Process Implementing Mass Exchange with a Counter Current Gas Permeation Membrane - Fischer, Carlos Daniel (2013)
In this paper, we propose changes in the design of a cyclohexane production process, following a mass exchange design heuristic developed in a previous work (Ind. Eng. Chem. Res.2011, 50 (11), 6849-6859). In the study case considered, an optimal design was obtained which exhibits a significant 40.08% reduction in the power of the compressor that recycles unreacted reagents, and a respectable 3.59% reduction of the hydrogen consumption, resulting in an increase of the plant Net Annual Income of a 1.31%. These results highlight the importance of considering a mass exchange between the input and output streams from the reactor, at the time of synthesizing a new process.